Epilepsy Patients at Suicidal Risk with Psychological Distress, Cognitive Failure and Perceived Social Support (Medical Forum Monthly, 2024)
Objectives: Core objective of present study was to explore the relationships between Suicidal risk, Psychological Distress, Perceived Social Support and Cognitive failure among the individuals with epilepsy and to find out gender differences (if any) on all variables.Study Design: Co-relational research study.Place and Duration of Study: This study was conducted at the Department of Applied Psychology, Bahauddin Zakariya University, Multan from 15th January, 2016 to 22nd March, 2016.Materials and Methods: Correlational research design was used for the present study. Total N=80 (both men and women) participants (all were diagnosed epilepsy patients) were recruited from different hospitals (Nishtar , CMH and Ibn-e-Seena hospital) of Multan, Pakistan by using purposive and convenient sampling technique. Data was collected from participants on Suicidal risk, Psychological Distress, Perceived Social Support and Cognitive failure by using relevant valid and reliable scales.Results: It was revealed that psychological distress, cognitive failure were positively associated with suicide risk whereas perceived social support negatively correlated with suicidal risk among individuals with epilepsy. Furthermore, perceived social support negatively related with psychological distress and cognition failure. Significant gender differences were found on Suicidal risk, Psychological Distress, Perceived Social Support and Cognitive failure in individuals with epilepsy.Conclusion: It was concluded that psychological distress and cognitive failure exacerbate the chance of suicidal risk whereas social support play vital role in decreasing the suicide risk, psychological distress and cognitive failure among epilepsy patients. So, the pertinent importance should be paid to the element of social support to enhance the overall quality of psychological health of people with epilepsy.